The role of associative learning and fear in the development of chronic pain – a comparison of chronic pain and post-traumatic stress disorder. (October 2014) - Sueki, D. G.; Dunleavy, K.; Puentedura, E. J.; Spielholz, N. I.; Cheng, M. S.
<x content-type="archive" xml:space="preserve">Abstract</x> Background: Associative learning is the theory that two stimuli can be paired to produce similar behavioral responses. In this model, a previously innocuous stimulus can become paired with a noxious stimulus to a point that this previously innocuous stimulus can result in the perception of pain. Objectives: This review discusses concepts related to neural activation and structural alterations in the presence of both chronic pain and post-traumatic stress disorder (PTSD). The role of associative learning and protective memory-based behavioral responses in the perception of pain is explored to provide a framework to inform clinical management of individuals with chronic pain and will be linked to the presence of actual or perceived threat or fear. Major Findings: Current research demonstrates that in individuals with chronic pain, cortical and subcortical processing of information shifts from normal nocioceptive processing areas to the medial prefrontal, anterior cingulate, and insular cortices, as well as the hippocampus (Hip) regions, all of which also show dysregulation, signs of gray matter atrophy, and changes in epigenetic coding. Because these regions are involved in memory, emotional processing, learning, and conditioning, it is reasonable to suggest that associative learning may be involved in the processing of both pain and PTSD. Conclusions: Clinically, rehabilitation paradigms that incorporate early intervention, positive expectation, therapeutic neuroscience education, visual imagery, movement retraining, and manual therapy all have the potential to change not only pain behavior but also the neural circuitry, epigenetic coding, and cortical morphology underlying chronic pain.